К питанию птиц открытых пространств Украины - Есилевская, М.А.; Медведев, С.И. (Вестник зоологии, 1974)
Analysis of 175 stomaches contents in four species of Alaudidae and three species of Motacillidae made it possible to establish that in their food there is a great number of insects-pests. As most birds of the studied species are the background of ornithofauna in the open areas, they serve as an essential regulator of the pests' quantity in the fields, pastures and in areas neighbouring the fields.
Consideration of birds' activity as a natural factor of the pests quantity regulation is of great importance for organization of biological methods for pest control.